The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1109/86.547944
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying characteristics of visually induced postural sway

Abstract: To study potential time-varying dynamics of postural sway as measured via center-of-pressure (COP) under the feet, we applied time-frequency analysis to COP data from ten vestibularly impaired subjects and 13 nonimpaired controls, during quiet stance and in response to visual perturbation. This analysis revealed that 1) the spectral characteristics of COP change over time; 2) there are time-dependent and frequency-dependent differences in COP between impaired and nonimpaired populations during visual perturbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 24 publications
2
23
1
Order By: Relevance
“…For the 0.3 Hz scene movement, COP power was calculated within the 0.25-0.35 Hz frequency band. This technique measures sway in response to the scene movement (entrainment) and not generalized destabilization (Redfern & Furman, 1994;Loughlin & Redfern, 1996).…”
Section: Data Processing and Statistical Analysesmentioning
confidence: 99%
“…For the 0.3 Hz scene movement, COP power was calculated within the 0.25-0.35 Hz frequency band. This technique measures sway in response to the scene movement (entrainment) and not generalized destabilization (Redfern & Furman, 1994;Loughlin & Redfern, 1996).…”
Section: Data Processing and Statistical Analysesmentioning
confidence: 99%
“…Med., 2008, 216 (3), 277-285. © 2008 Visual perception is closely related to postural control and provides afferent feedback regarding postural sway to the cerebellum (Loughlin et al 1996;Loughlin and Redfern, 2001). Visual function is mainly evaluated via visual acuity and the visual fields (Margolis et al 2002).…”
mentioning
confidence: 99%
“…We have demonstrated that a time domain statistical model provides a more sensitive measure of postural organization than the more commonly used measure of center of pressure (Jonsson et al 2004(Jonsson et al , 2005Barbier et al 2003;Colobert et al 2006;Betker et al 2006) which is a global outcome measure and does not fully describe segmental postural behaviors. A perturbed postural system does not necessarily respond only at the driving frequency (Creath et al 2005;Loughlin et al 1996;Loughlin and Redfern 2001) and one of the advantages of this statistical model is that it is not limited to describing behavior just at the driving frequency. We believe that this model will enable us to explore the full bandwidth of adaptive postural control during complex tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that sway during quiet stance (Carroll and Freedman 1993;Collins and De Luca 1993;Schumann et al 1995;Loughlin et al 1996;Creath et al 2005;Guelton et al 2008) exhibits non-linear and timevarying behavior suggesting shifting mechanisms for control. Furthermore, Creath et al (2005) have proposed that the whole body behaves like a multi-link pendulum during quiet stance and has two simultaneously co-existing excitable modes.…”
Section: Introductionmentioning
confidence: 99%